The effect of socio-demographic characteristics on the burnout syndrome of nurses in Republic of Srpska during the COVID-19 pandemic - Ljubiša Kucurski; Tamara Popović; Dijana Djurić; Jelena Pavlović; Ljiljana Savić; Srdjan Živanović; Ljubinka Božić Majstorović; Sanja Tomić (Биомедицинска истраживања, 2024)
Introduction: Nursing is a high-risk profession for burnout due to deadlines, workload, close patient and family interac tions, and supervisor demands. This study aims to assess the frequency of burnout among nurses in COVID-19 and other departments during the pandemic. Methods: This cross-sectional study, conducted from November 8 to December 1, 2021, included 246 nurses from COVID-19 and other departments. Two questionnaires were used: a sociodemographic survey and the Maslach Burnout Inventory. Results: Statistically significant differences were found in emotional exhaustion (Z=-3.518; p?0.001), depersonaliza tion (Z=-2.257; p=0.024), and total burnout score (Z=-4.330; p?0.001) between nurses in COVID-19 wards and those in other departments. Data suggest that nurses with less than 10 years of experience are at higher risk of burnout than those with 10-30 years of experience. Conclusion: Nurses in COVID-19 wards exhibited higher emotional exhaustion and depersonalization compared to those in other departments.
Keywords: burnout syndrome; stress; nursing; SARS-CoV-2